Ethnic Differences in Realising Desires to Leave the Neighbourhood - Sanne Boschman; Reinout Kleinhans; Maarten van Ham (Institute for the Study of Labor (IZA), 2014)
Selective mobility into and out of neighbourhoods is one of the driving forces of segregation. Empirical research has revealed who wants to leave certain types of neighbourhoods or who leaves certain neighbourhoods. A factor which has received little attention so far is that some residents will have a desire to leave their neighbourhood, but are unable to do so. The residential mobility literature shows that the discrepancy between moving desires and actual mobility is larger for ethnic minorities than for natives. This paper uses a unique combination of register data and survey data. We combine data from a large housing survey in the Netherlands (WoON) with longitudinal register data from the Netherlands (SSB), which contains individual level information on residential mobility histories. This allows us to study which households with a wish to leave their neighbourhood are actually successful, and to which neighbourhoods they move. A more thorough insight in who wants to leave which neighbourhoods but is unable to do so will contribute to a better understanding of the drivers of segregation, especially in the context of the debate on voluntary segregation versus segregation due to a lack of choice. We find that ethnic minority groups are less likely to realise a desire to leave their neighbourhood and that if they succeed in moving from an ethnic minority concentration or poverty neighbourhood, they are more likely to end up in another minority concentration or poverty neighbourhood than native residents.
Keywords: J15; R23; 330; ethnic minorities; selective mobility; segregation; neighbourhoods; moving desires